Embodying the monster : encounters with the vulnerable self - Shildrick, Margrit (Theory, culture & society (Unnumbered), 2002)
Margrit Shildrick's exploration of the monstrous reveals how humans register concepts of bodily normality and perfection. The author calls upon society to rethink the monstrous, not as an abnormal category, but as a condition of attractiveness.